An Unaccountable Love: Healing and Sacrifice in Post-Genocide Rwanda. Issue 1 (1st March 2022) - Itzhak, Nofit
Abstract: What does a consideration of the place of grace in the therapeutic relationship have to add to our understanding of the healing process? This article explores the experience of bereavement and healing in the aftermath of loss among members of a Catholic Charismatic community in Rwanda. Considering cases in which divine healing is experienced as either having succeeded or having failed, I argue that the healing process involves acts of sacrifice and gifting, taking place between the mourner, God, and social others, and that the central sacrificial gesture constituting this process is the sacrifice of the self as lived prior to loss. I suggest that in order to understand gifting and sacrifice's therapeutic potential, we must read them as acts anchored in grace or gratuity.